Digital Transformation and the Economics of Banking Economic, Institutional, and Social Dimensions - Łasak, Piotr; Williams, Jonathan (Taylor & Francis, 2024)
Banking; digital transformation; digitalization; financial institutions; FinTech; innovation and technology management; Insurance; CBDC, sustainability, privacy, central bank, digital currency, FinTech